2016
DOI: 10.1136/heartjnl-2016-309667
|View full text |Cite
|
Sign up to set email alerts
|

Cell-matrix mechanics and pattern formation in inflammatory cardiovascular calcification

Abstract: Calcific diseases of the cardiovascular system, such as atherosclerotic calcification and calcific aortic valve disease, are widespread and clinically significant, causing substantial morbidity and mortality. Vascular cells, like bone cells, interact with their matrix substrate not only through molecular signals, but also through biomechanical signals, such as traction forces transmitted from cytoskeleton to matrix. The interaction of contractile vascular cells with their matrix may be one of the most importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 70 publications
1
34
0
2
Order By: Relevance
“…The entire cardiovascular system is vulnerable to pathological calcification [1], and vascular disease, such as atherosclerosis, arteriosclerosis and diabetic vasculopathy, is frequently complicated by calcification [2]. Calcification in arteries can be widespread, and the prevalence increases with age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The entire cardiovascular system is vulnerable to pathological calcification [1], and vascular disease, such as atherosclerosis, arteriosclerosis and diabetic vasculopathy, is frequently complicated by calcification [2]. Calcification in arteries can be widespread, and the prevalence increases with age.…”
Section: Introductionmentioning
confidence: 99%
“…Another common site of calcification is the aortic valve, termed calcific aortic valvular disease (CAVD), which has severe consequences. Approximately 40% of people over the age of 70 years have mild calcification of the aortic valve, with over 10% having severe calcification [1]. Lastly, calcification of arterioles of the skin and other organs can lead to localized infarction and ischemia, including ischemic bowel and calciphylaxis [4].…”
Section: Introductionmentioning
confidence: 99%
“…In an established mouse model of acquired AS, valve interstitial cells undergo transdifferentiation into myofibroblasts, which express α‐SMA and produce interstitial collagen 16. Myofibroblasts may then transdifferentiate further into osteoblast‐like cells, which produce matrix calcification 24. Similar processes occur in diseased human valves, in which α‐SMA and calcification colocalize 25.…”
Section: Discussionmentioning
confidence: 98%
“…Vascular cells, like bone cells, interact with their matrix substrate through molecular signals and biomechanical signals to control pathological calcification of the artery wall and cardiac valves (4). The present study by Pallai et al also showed involvement of cellmatrix mechanics in pathological heart calcificationthat CFs express ENPP1, and ENPP1-generated PPi in heart increases mineralization via hydrolysis of PPi to generate Pi by tissue non-specific alkaline phosphatase (TANP) and subsequent calcium hydroxyapatite formation in extracellular matrix to develop post-injury cardiac calcification.…”
Section: Editorialmentioning
confidence: 99%
“…Any abnormality of calcium metabolism can lead to metastatic myocardial calcification, including chronic renal failure, bone destruction or increased bone turnover, hyperparathyroidism, and vitamin D-related disorders. Calcification of the cardiovascular system, such as aortic valve and vascular calcification, has important clinical significance (4). Myocardial calcification is an unusual form of soft tissue calcification characterized by abnormal calcific accumulation within the heart muscle which can occur in the absence of calcification of vessels, valves, or other organs (5).…”
mentioning
confidence: 99%